Serum carotenoids reduce progression of early atherosclerosis in the carotid artery wall among Eastern Finnish men. - Jouni Karppi (Public Library of Science (PLoS), 2013)
Background Several previous epidemiologic studies have shown that high blood levels of carotenoids may be protective against early atherosclerosis, but results have been inconsistent. We assessed the association between atherosclerotic progression, measured by intima-media thickness of the common carotid artery wall, and serum levels of carotenoids. Methods We studied the effect of carotenoids on progression of early atherosclerosis in a population-based study. The association between concentrations of serum carotenoids, and intima-media thickness of the common carotid artery wall was explored in 840 middle-aged men (aged 46-65 years) from Eastern Finland. Ultrasonography of the common carotid arteries were performed at baseline and 7-year follow-up. Serum levels of carotenoids were analyzed at baseline. Changes in mean and maximum intima media thickness of carotid artery wall were related to baseline serum carotenoid levels in covariance analyses adjusted for covariates. Results In a covariance analysis with adjustment for age, ultrasound sonographer, maximum intima media thickness, examination year, body mass index, systolic blood pressure, smoking, physical activity, serum LDL cholesterol, family history of coronary heart disease, antihypertensive medication and serum high sensitivity C-reactive protein, 7-year change in maximum intima media thickness was inversely associated with lycopene (p = 0.005), α-carotene (p = 0.002) and β-carotene (p = 0.019), respectively. Conclusions The present study shows that high serum concentrations of carotenoids may be protective against early atherosclerosis.